Assessment of Blastability Index in massive limestone from Rawang Quarry, Selangor - Hamidun, Haizam (2023)
The demand for construction materials produced by quarry rises in tandem with urbanization. Selangor is one of the highly populated states in Malaysia with residential projects now located very close or even next to quarry. Due to the fact that limestone consists of numerous weak spots in rock masses, it has always been thought that limestone quarry operation is riskier than common granite quarry operations. Geologically, limestone formation in Rawang sits uncomfortably on top of the older metamorphic rocks with its own unique joints system. The goal of the study was to identify the rock mass properties in massive limestone profile from a quarry in Rawang, Selangor and its relation to blast design as well as effects on the surrounding environment due to blasting. For a systematic study, the quarry face was divided into four (4) sections i.e., section A, section B, section C, and section D. The site mapping showed significant findings where section A is considered high potential of having excessive flyrock as it has the most joint number (J), joint plane spacing (JPS) and joint aperture (JA) with 31, 559.8 mm and 28.5 mm, respectively. When blasthole intersected with many joints, explosive energy escape through joints causing sudden drop in blasthole pressure and open joints extend up to the face thus creating high possibility of flyrock during blasting. The degree of difficulty to fragment rock in terms of Blastability Index (BI) was also calculated based on the geological mapping data. The results show that BI ranged from 49.18 to 59.26 percent throughout all study sections indicating that the rock mass at the quarry was easy to be blasted as per Blastibility Quality System (BQS). The calculated BI was also justified the suitability of blast design used during blasting at the quarry. The new site constants i.e., K and β for the study area were also calculated with USBM predictor at 40 and 1.0, while Langefors- Kihlstrom (LK) predictor at 6.8 and 1.07, respectively. Although at maximum charge per delay (Wmax) the blasting was being carried out safely with very minimal effects to the surrounding areas. Finally, correlations between all earlier findings such as BI, blast design and environment effects i.e., peak particle velocity (PPV) measured and predicted were justified the significant relation of rock mass properties and ground vibration effect due to blasting operation at the quarry.